What makes accounting interesting for learners? Viewpoint of a teacher from India - Sivasankaran Narayanasamy (Asian Journal of Accounting Research, 2020)
The article aims to share the viewpoint of the author on the impact of the innovative teaching pedagogy adopted by him in teaching the accounting courses on the satisfaction of the participants in a premier Indian Business School.The experiment was carried over by introducing an innovative teaching approach by the author among the first-year participants of the Management Program. At the end of the experiment, the participants were asked to rate the teaching approach on a five-point scale besides offering the qualitative feedback on the impact of the experiment on their learning outcomes.The paper concludes that the participants were highly satisfied with the teaching approach adopted by the author.The study contributes to the theory and practitioners on accounting education in many ways. First, it is offering evidence on the impact of teaching pedagogy on the satisfaction of the participants of the accounting courses of an emerging market business school. Second, the accounting educators of the emerging countries may replicate the experiment in their institutes. Third, the educators of other courses in the business schools may make an effort to measure the impact of the teaching approach on the feedback of their learners.